Left atrial mural endocarditis in the absence of significant structural heart disease - Waddah Malas; Mashaal Ikram; Max Ruge; Puja K. Mehta; Stuart Chen (American Heart Journal Plus, 2021)
Primary mural endocarditis without valvular involvement is rare and most often involves the ventricular endocardium. Left atrial mural endocarditis is an extremely rare subset of infective endocarditis. We describe a case of a young woman with left atrial mural endocarditis without significant structural or valvular heart disease.